Ocorrência de patógenos de origem bacteriana e viral e marcadores de virulência de Escherichia coli e Rhodococcus equi isolados das fezes de aves silvestres de cativiero da fauna brasileira - Morais, Amanda Bonalume Cordeiro de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present study investigated the occurrence of Escherichia coli, Rhodococcus equi, Salmonella sp., Coronavirus and Rotavirus in the feces of Passeriformes and psittaciformes belonging to Brazilian wildlife, from 29 different species, without enteric signs. Virulence markers were also investigated in strains of E. coli (cnf1, hlyA, papC, papGI, papGII, papGIII, fimH, afa, sfa, iucD, usp, vt1, vt2, eae, k88) and R. equi (vapA and vapB genes). The birds used in the study came from the Centro de Medicina e Pesquisa em Animais Silvestres (CEMPAS) FMVZ - UNESP / Botucatu, SP, Parque Zoológico Municipal Quinzinho de Barros (PZMQB) Sorocaba, SP and private breeders with birds recorded in Instituto Brasileiro do Meio Ambiente e dos Recursos Renováveis (IBAMA) from Botucatu region, SP. Of the total 152 fecal samples evaluated were isolated 46 (30.26%) strains of E. coli. From these, 37 (80%) were from psittaciformes samples and 9 (20%) of Passeriformes. There was a statistical difference (p <0.05) between groups with greater isolation of E. coli in psittaciformes. Among the virulence markers of E. coli were detected the genes fimH (58,69%) and eae (4,34%). Were isolated 2 (1.32%) R. equi strains, all from psittaciformes. Among these R. equi isolates any vapA and vapB genes associated with virulence were founded. Genetic material of bovine Rotavirus was found in three (1.97%) psittaciformes samples. Salmonella sp. and Coronavírus weren’t identified in any of the sampled birds. The presence of E. coli, R. equi and Rotavirus in fecal samples of wild birds without enteric signs from Brazil wildlife, reinforces the potential of these birds as a reservoirs of pathogens of enteric elimination for humans, due to the presence of these animals in the domestic and peridomestic, environment of human

O presente estudo investigou a ocorrência de Escherichia coli, Rhodococcus equi, Salmonella sp., Coronavírus e Rotavírus nas fezes de Passeriformes e Psitaciformes pertencentes à fauna nacional, de 29 diferentes espécies, sem sinais entéricos. Foram investigados também marcadores de virulência nas linhagens de E. coli (cnf1, hly, papC, papGI, papGII, papGIII, fimH, afa, sfa, iucD, usp, vt1, vt2, eae, k88) e R. equi (genes vapA e vapB). As aves utilizadas no estudo foram provenientes do Centro de Medicina e Pesquisa em Animais Silvestres (CEMPAS) FMVZ - UNESP/ Botucatu, SP, do Parque Zoológico Municipal “Quinzinho de Barros” (PZMQB) de Sorocaba, SP e de criadores particulares com aves registradas no Instituto Brasileiro do Meio Ambiente e dos Recursos Renováveis (IBAMA) da região de Botucatu, SP. Do total de 152 amostras avaliadas foram isoladas 46 (30,26%) linhagens de E. coli das quais 37 (80%) foram provenientes de amostras de Psitaciformes e 9 (20%) de Passeriformes. Houve diferença significante (p<0,05) entre os grupos para o maior isolamento de E. coli nos Psitaciformes. Dentre os marcadores de virulência de E. coli foram detectados os genes fim H (58,69%) e eae (4,34%). Foram isoladas 2 (1,32%) linhagens de R. equi, todas de Psitaciformes. Nestes isolados de R. equi não foram identificados os genes vapA e vapB associados à virulência. Foi encontrado material genético de Rotavírus bovino em três (1,97%) amostras de Psitaciformes. Salmonella sp. e Coronavírus não foram identificados nas aves amostradas. A presença de E. coli, R. equi e Rotavírus em amostras de fezes de aves silvestres, sem sinais entéricos, reforça o potencial destas espécies de servirem como reservatórios de patógenos de eliminação entérica para os humanos, devido à presença destes animais no ambiente domiciliar e peridomiciliar
Keywords: Escherichia coli; Pesquisa ornitologica; Rotavirus; Rhodococcus equi